2011
DOI: 10.1007/s00125-011-2068-x
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of lipid-induced insulin resistance in rat skeletal muscle by overexpression of Pgc-1β involves reductions in long-chain acyl-CoA levels and oxidative stress

Abstract: Aims/Hypothesis To determine if acute overexpression of peroxisome proliferator-activated receptor, gamma, coactivator 1 beta (Pgc-1β [also known as Ppargc1b]) in skeletal muscle improves insulin action in a rodent model of dietinduced insulin resistance. Methods Rats were fed either a low-fat or high-fat diet (HFD) for 4 weeks. In vivo electroporation was used to overexpress Pgc-1β in the tibialis cranialis (TC) and extensor digitorum longus (EDL) muscles. Downstream effects of Pgc-1β on markers of mitochondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
49
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 51 publications
2
49
2
Order By: Relevance
“…Diacylglycerols (DGs) have been proposed to impair insulin action by activating protein kinase C isoforms and antagonising insulin signalling [5]. Elevated DGs in muscle and liver are associated with insulin resistance in humans [5,6] and animals [7,8]. Genetic manipulations in rodents that alter DG levels also support a role for this lipid intermediate as an important mediator of insulin action [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diacylglycerols (DGs) have been proposed to impair insulin action by activating protein kinase C isoforms and antagonising insulin signalling [5]. Elevated DGs in muscle and liver are associated with insulin resistance in humans [5,6] and animals [7,8]. Genetic manipulations in rodents that alter DG levels also support a role for this lipid intermediate as an important mediator of insulin action [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Ceramide is increased in tissues of insulin-resistant humans and rodents [8,13,14] and reduction of ceramide levels is associated with improved insulin sensitivity [13,15,16]. Importantly, though many studies have demonstrated a link between insulin resistance and levels of DG and ceramides, there are also several instances where alterations in insulin action and bioactive lipid content in tissues do not correlate and thus there is still substantial controversy in this area [8,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The consequence of a Pgc-1α/Pgc-1β muscle-specific double knockout approach remains unknown. In contrast, the data provided by Wright et al [2] suggest a protective role for PGC-1β against high-fat-diet-induced insulin resistance in skeletal muscle. Similarly, the moderate and acute modulation of electroporated PGC-1α in muscle resulted in improvement of insulin sensitivity in the muscle of lean and obese Zucker rats [11].…”
mentioning
confidence: 79%
“…While relative level of physical activity is the dominant regulator of Pgc-1α gene expression in skeletal muscle, transcriptional control of Pgc-1β (also known as Ppargc1b) seems less straightforward, and different effects of exercise, denervation, dietary restriction, bariatric surgery, obesity and insulin stimulation on muscle Pgc-1β mRNA levels have been described, some with conflicting results in different experimental settings (summarised in references [1][2][3][4]). The elegant study by Wright et al published in this issue of Diabetologia [2] sheds more light on the important role of PGC-1β in muscle physiology. Pgc-1β was overexpressed in electroporated tibialis cranialis and extensor digitorum longus muscles of low-fat-or high-fat-fed rats (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation